SOLUTIONS TO IMPROVE THE QUALITY OF PHYSICAL EDUCATION - Phi Yen, Nguyen; Le Van Ninh; Ha Ngoc Huy (Britain International for Academic Research (BIAR) Publisher, 2023)
Physical education in schools is an extremely important and fundamental part of physical education and sports activities that play a role in promoting health and physical fitness for students, actively contributing to the training of students. , training people for comprehensive development to build and protect the Fatherland. Physical education is one of the comprehensive educational goals of the Party and State of Vietnam, within the national education system. Physical education is understood as: “The pedagogical process aimed at educating and training the young generation, perfecting physical and personality, improving working ability, and prolonging human life”. Physical education, like other types of education, is a pedagogical process with all its characteristics, with the leading role of the pedagogue, organizing the pedagogue's activities in accordance with the students. , in accordance with pedagogical principles. Based on references to colleagues' articles and State legal documents, this article will focus on solutions that contribute to improving the quality of physical education at the University of Transport and Communication - Campus in Ho Chi Minh City (UTC2)